2005
DOI: 10.1007/s11258-005-9036-9
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory and plant competition reduce mountain beech seedling growth and establishment in New Zealand

Abstract: The effect of herbivory and resource availability on the competitive ability of different plant species has been an area of intense debate amongst plant ecologists for at least two decades, but the interactive effects of herbivory and plant competition between woody and herbaceous plants are rarely studied and theory is poorly developed. This study used experimental manipulations on transplanted and naturally occurring mountain beech (Nothofagus solandri var. cliffortioides) seedlings to show the effects of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 72 publications
0
19
1
Order By: Relevance
“…Deer-browsed plants were over 4 times more likely to die in light gaps than in the understory. In contrast, tree seedlings have been shown to have lower survival in response to clipping or mammalian browsing in understory habitats in many species (Blundell and Peart 2001;Milbrath 2008;Norghauer et al 2008) but not all (Husheer et al 2006). The diVerence in survival found here was caused by disparities in the extent of deer-inXicted damage to lightgap and understory plants.…”
Section: Discussioncontrasting
confidence: 58%
“…Deer-browsed plants were over 4 times more likely to die in light gaps than in the understory. In contrast, tree seedlings have been shown to have lower survival in response to clipping or mammalian browsing in understory habitats in many species (Blundell and Peart 2001;Milbrath 2008;Norghauer et al 2008) but not all (Husheer et al 2006). The diVerence in survival found here was caused by disparities in the extent of deer-inXicted damage to lightgap and understory plants.…”
Section: Discussioncontrasting
confidence: 58%
“…Those studies mainly show that herbivory by deer and other large mammalian herbivores have strong negative effects on plant growth, reproduction, survival, and terrestrial carbon storage (Crête et al 2001, Russell et al 2001, Côté et al 2004, Knight et al 2009, MacDougall et al 2010. Herbivory on younger life cycle stage trees will eventually influence the structure of the future mature forest (Husheer et al 2006, Long et al 2007 Effects of deer on the growth of mature canopy trees have rarely been reported. The few studies showing impacts of deer on larger tree species include in their definition of mature individuals from young life stages or from smaller size classes with which deer can interact directly through browsing or other means.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, deer (Cervidae) populations have increased dramatically throughout many areas of the world, including North America (Horsley et al 2003), Europe (Apollonio et al 2010), Asia (Tsujino andYumoto 2004, Suzuki et al 2008), and Oceania (Platt et al 2004, Husheer et al 2006. Population increases have been driven primarily by forest clearing (Dale 1997), reduction of predator populations (Mladenoff et al 1999), and milder winter temperatures (Dumont et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Below-ground competition was probably low due to the nutrient rich seed-bed plots and permanent water supply in our experiment. Under such reduced stress conditions, enhanced shoot or stem growth is to be expected (Davis et al 1999;Husheer et al 2006). However, the positive effect of a low surrounding grassland vegetation in our experiment may not be equally present in permanently grazed, natural conditions due to associated palatability (i.e.…”
Section: Vegetation Structure and Grazing Interactionmentioning
confidence: 99%